Yield and horticultural performance of seed-oil pumpkin in south Florida - Geoffrey Meru; Yuqing Fu (EDIS)
Naked seeds derived from ‘naked-seed’ pumpkin (Cucurbita pepo L.) are a popular ingredient in many snacks, breads, breakfast cereal, soups and other edible goods (Baxter et al. 2012; Loy 2004). Vegetable oil derived from the seed can be purchased by the bottle for culinary/ condiment use or as formulated capsules in health food stores (Stevenson et al. 2007). Unlike conventional hulled pumpkin seeds, naked seeds lack a complete seed coat, thus are preferred for snacking and oil production because they eliminate the need for manual de-hulling prior to use. Popularity of naked seed products is expected to increase in the US as the market for healthy foods increases. Pumpkin seed is rich in oil (50% w/w), protein (35%), unsaturated fatty acids (86%) (Meru et al. 2018), and antioxidants that have many health benefits, including a reduced risk of certain cancers (Lelley et al. 2009; Nesaretnam et al. 2007; Stevenson et al. 2007), treatment of enlarged prostate, and  lowering cholesterol levels (Fruhwirth and Hermetter 2007; Thompson and Grundy 2005). Despite growing popularity of pumpkin seeds in the US, a majority of naked seeds consumed in the US is imported; hence, the need to identify/ develop cultivars adapted to local growing conditions. This article reports yield and horticultural performance of two ‘naked-seed’ pumpkin cultivars under south Florida (Miami-Dade County) spring growing conditions.